Tissue Treg Secretomes and Transcription Factors Shared With Stem Cells Contribute to a Treg Niche to Maintain Treg-Ness With 80% Innate Immune Pathways, and Functions of Immunosuppression and Tissue Repair - Zhang, Ruijing; Xu, Keman; Shao, Ying; Sun, Yu; Saredy, Jason; Cutler, Elizabeth; Yao, Tian; Liu, Ming; Liu, Lu; Drummer IV, Charles; Lu, Yifan; Saaoud, Fatma; et al. (Frontiers in Immunology, 2021)
We used functional -omics angles and examined transcriptomic heterogeneity in CD4+Foxp3+ regulatory T cells (Treg) from spleen (s-Treg), lymph nodes (LN-Treg), intestine (int-Treg), and visceral adipose tissue (VAT-Treg), and made significant findings: 1) Five new shared Treg genes including NIBAN, TNFRSF1b, DUSP4,VAV2, and KLRG1, and 68 new signatures are identified. Among 27 signaling pathways shared in four tissue Treg, 22 pathways are innate immune pathways (81.5%); 2) s-Treg, LN-Treg, int-Treg, and VAT-Treg have zero, 49, 45, and 116 upregulated pathways, respectively; 3) 12, seven, and 15 out of 373 CD markers are identified as specific for LN-Treg, int-Treg, and VAT-Treg, respectively, which may initiate innate immune signaling; 4) seven, 49, 44, and 79 increased cytokines out of 1176 cytokines are identified for four Treg, respectively, suggesting that Treg have much more secretory proteins/cytokines than IL-10, TGF- and IL-35; 5) LN-Treg, int-Treg, and VAT-Treg have 13 additional secretory functions more than s-Treg, found by analyzing 1706 secretomic genes; 6) Two, 20, 25, and 43 increased transcription factors (TFs) out of 1496 TFs are identified four Treg, respectively; 7) LN-Treg and int-Treg have increased pyroptosis regulators but VAT-Treg have increased apoptosis regulators; 8) One, 15, 19 and 31 increased kinases out of 661 kinome are identified for s-Treg, LN-Treg, int-Treg, and VAT-Treg, respectively; 9) comparing with that of s-Treg, LN-Treg, int-Treg, and VAT-Treg increase activated cluster (clusters 1-3) markers; and decrease resting cluster (clusters 4-6) markers; and 10) Treg promote tissue repair by sharing secretomes and TFs AHR, ETV5, EGR1, and KLF4 with stem cells, suggesting that stem cell-shared master genes make tissue Treg as the first T cell type using a Treg niche to maintain their Treg-ness with 80% innate immune pathways, and triple functions of immunosuppression, tissue repair, and homeostasis maintenance. Our results have provided novel insights on the roles of innate immune pathways on Treg heterogeneity and new therapeutic targets for immunosuppression, tissue repair, cardiovascular diseases, chronic kidney disease, autoimmune diseases, transplantation, and cancers.